Optimalisasi Strategi Public Relations dalam Meningkatkan Citra Night Club Pink Panther di Jakarta - Grace Ketty Wilandar; Doddy Salman (Kiwari, 2026)
This study examines the digital public relations strategy implemented by Pink Panther PIK 2 on Instagram to shape its brand image among visitors and potential audiences. The research focuses on visual content, caption strategies, posting consistency, engagement patterns, and content differentiation as essential elements of online communication. Using a qualitative descriptive approach, data were collected through in-depth interviews and documentation of Instagram posts, including feed uploads, reels, and user interactions. The findings indicate that Pink Panther positions Instagram as its primary digital platform to enhance brand visibility, highlight differentiation, and manage audience perceptions. Content differentiation emerges as a key strategy, particularly in emphasizing permissive policies such as allowing customers to bring their own bottles, which distinguishes the club from competitors. The study also identifies a significant improvement in content quality, shifting from previously vulgar styled visuals to more curated, aesthetic, and professional content aligned with current digital branding trends. This transformation contributes to a stronger and more positive brand image, portraying Pink Panther as an exclusive, secure, and professionally managed entertainment venue. Overall, the research shows that strategic digital public relations on Instagram effectively supports brand image-building in the nightlife industry. Penelitian ini menganalisis strategi Digital Public Relations yang diterapkan Pink Panther PIK 2 melalui Instagram dalam membangun citra di kalangan pengunjung maupun calon audiens. Fokus penelitian diarahkan pada pemanfaatan konten visual, strategi penulisan caption, konsistensi unggahan, pola interaksi digital, serta diferensiasi konten sebagai elemen utama komunikasi publik yang dijalankan secara daring. Penelitian ini menggunakan pendekatan deskriptif kualitatif dengan teknik pengumpulan data berupa wawancara mendalam dan dokumentasi konten Instagram, mencakup unggahan feed, reels, serta interaksi pengguna. Temuan menunjukkan bahwa Pink Panther menempatkan Instagram sebagai kanal digital utama untuk memperkuat visibilitas merek, menonjolkan diferensiasi, serta mengelola persepsi audiens. Diferensiasi konten menjadi strategi yang paling menonjol, terutama melalui penekanan pada kebijakan yang membedakan Pink Panther dari klub lain, seperti diperbolehkannya pengunjung membawa botol minuman dari luar. Penelitian juga menemukan adanya peningkatan kualitas konten, dari gaya yang sebelumnya lebih vulgar menjadi visual yang lebih terkurasi, estetis, dan profesional sesuai tren branding digital saat ini. Transformasi ini berkontribusi pada pembentukan citra Pink Panther sebagai tempat hiburan yang eksklusif, aman, dan dikelola secara profesional. Secara keseluruhan, strategi Digital Public Relations melalui Instagram terbukti efektif dalam mendukung pembangunan citra di industri hiburan malam.